2018
DOI: 10.31062/agrom.v25i1.26263
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da quantidade e frequência de chuva no rendimento da soja

Abstract: A soja (Glycine max L.), importante cultura no cenário agrícola brasileiro, apresenta elevada variação interanual do rendimento de grãos no Estado do Rio Grande do Sul (RS). Geralmente, a maior parte desta inconstância é devido à irregularidade da quantidade e frequência da precipitação. Neste trabalho, correlacionou-se o rendimento de grãos de soja em seis municípios do RS de 2005 a 2012 com o acumulo da precipitação trimestral de outubro a abril e avaliou-se também o número de dias com chuva e consecutivos s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…Araújo et al (2014) identified a spatial association between soybean productivity and agrometeorological variables such as rainfall, temperature and global solar radiation. Radin et al (2017) verified the correlation between soybean productivity and rainfall accumulation during the crop's vegetative cycle in municipalities of Rio Grande do Sul, from 2005 to 2012. The results showed that the variation in productivity could be explained by rainfall, where the occurrence of consecutive days without rain during the crop cycle exerted a negative impact on soybean productivity.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Araújo et al (2014) identified a spatial association between soybean productivity and agrometeorological variables such as rainfall, temperature and global solar radiation. Radin et al (2017) verified the correlation between soybean productivity and rainfall accumulation during the crop's vegetative cycle in municipalities of Rio Grande do Sul, from 2005 to 2012. The results showed that the variation in productivity could be explained by rainfall, where the occurrence of consecutive days without rain during the crop cycle exerted a negative impact on soybean productivity.…”
Section: Introductionmentioning
confidence: 59%
“…Several studies have evaluated the influence of agrometeorological variables on soybean productivity (Araújo et al, 2014;Radin et al, 2017;Grzegozewski et al, 2017). Araújo et al (2014) identified a spatial association between soybean productivity and agrometeorological variables such as rainfall, temperature and global solar radiation.…”
Section: Introductionmentioning
confidence: 99%
“…2d). This means that the crop management applied in this region could explore more the environmental conditions than other regions, including the interaction with climate (Radin et al 2017;Hampf et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Mesmo com a evolução tecnológica da agricultura e das diferentes técnicas de manejo (rotação de culturas, cobertura permanente do solo com material vegetal), que buscam minimizar os impactos das variações dos estresses hídricos no rendimento das culturas, períodos prolongados de estiagens ou precipitações excessivas podem impactar fortemente uma safra agrícola (Radin et al, 2017;Zanon et al, 2018). Sendo a soja altamente dependente da precipitação registrada durante o seu ciclo de desenvolvimento, a identificação de mecanismos de teleconexão que impactam a precipitação e, consequentemente a produtividade de soja, faz-se necessária para aprimorar as estimativas de safra, fornecendo mais subsídios no momento em que é realizado o planejamento das lavouras de soja.…”
Section: Introductionunclassified